Applying X-ray Microtomography to Study Microbial-Induced Self-Healing of Geopolymers - Jadin Zam S. Doctolero (AIDIC Servizi S.r.l., 2021)
Geopolymers are one of the emerging sustainable materials for the building and construction industry. They are inorganic polymers produced from aluminosilicate waste materials such as coal fly ash and have been shown to have a lower carbon footprint as compared with Portland cement. However, geopolymers are a cementitious material like Portland cement-based concrete and are thus brittle and prone to develop cracks. The use of microorganisms has recently been considered as an approach to improve the self-healing capability of geopolymers through microbial-induced calcite precipitation. The application of X-ray microtomography to observe the potential of self-healing of bio-geopolymers is explored in this study. Bio-geopolymers were produced from the alkali activation of coal fly ash and mixed with self-healing agents using a form of biochar-immobilized spores of B. sphaericus and B. thuringiensis. These bio-geopolymers were then scanned using micro-focus XCT to obtain a visualization of the microstructure of the material via a non-destructive 3D imaging technique after self-healing. Coupled with image analysis, quantification of the segmented data allowed further investigation of self-healing through comparison with the other self-healing characterization method.